2017
DOI: 10.1186/s40880-016-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

For robust big data analyses: a collection of 150 important pro-metastatic genes

Abstract: Metastasis is the greatest contributor to cancer-related death. In the era of precision medicine, it is essential to predict and to prevent the spread of cancer cells to significantly improve patient survival. Thanks to the application of a variety of high-throughput technologies, accumulating big data enables researchers and clinicians to identify aggressive tumors as well as patients with a high risk of cancer metastasis. However, there have been few large-scale gene collection studies to enable metastasis-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 154 publications
0
16
0
Order By: Relevance
“…Consistent with this previous study, we found downregulated RWDD4 inhibited TCC cell proliferation, migration and invasion in vitro. Based on large-scale data analyses, cancer metastasis has been established as a complicated procedure driven by more than 100 genes (24,25). Whether and how RWDD4 is involved in the miR-506-mediated regulation of EMT remains to be clarified in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this previous study, we found downregulated RWDD4 inhibited TCC cell proliferation, migration and invasion in vitro. Based on large-scale data analyses, cancer metastasis has been established as a complicated procedure driven by more than 100 genes (24,25). Whether and how RWDD4 is involved in the miR-506-mediated regulation of EMT remains to be clarified in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the gene E2F1 is an important transcription factor and is one of the most important pro-metastatic genes. Mei et al (48) observed that E2F1 had a significant effect on the prognosis of patients and was closely associated with patient survival, suggesting that E2F1 has an important role in the progression of clear cell renal cell carcinoma and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are >20 genes in the S100 family and some of these are considered as tumor markers (7). A recent study suggested that S100A4 and S100P, which are members of the S100 family, serve as pro-metastatic factors (8). S100B (also known as S100beta) also belongs to the S100 family.…”
Section: Introductionmentioning
confidence: 99%